THE INFLUENCE OF TEACHER ABILITY TO CONDUCT LEARNING EVALUATION ON LEARNING OBJECTIVES OF CREED MORALS - Hairun Nisa. Betti Megawati, Muhammad Taufiqrrahman (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study seeks to examine the impact of teachers' ability toconduct learning evaluations on the achievement of Akidah Akhlak learningobjectives at MAS Al Washliyah Sei Berombang, Labuhanbatu. This researchadopts a quantitative approach, utilizing questionnaires, observations, anddocumentation for data collection. Data analysis is conducted through hypothesistesting, employing the product-moment correlation formula and the chi-squaretest. The findings reveal a significant correlation between the teacher's ability toevaluate the learning objectives of Aqidah Akhlak, with a correlation coefficientof 0.653, indicating a strong relationship. The coefficient of determination showsthat 38.31% of the variance is explained by this relationship. Additionally, thechi-square value (x²) was found to be 15.05. The contingency coefficient (C),calculated as 0.615 with a maximum value of 0.816, r